Baby cry recognition is independent of motherhood but improved by experience and exposure. Issue 1921 (26th February 2020) - Bouchet, Hélène; Plat, Aurélie; Levréro, Florence; Reby, David; Patural, Hugues; Mathevon, Nicolas
Abstract : Neurobiological changes affecting new mothers are known to support the development of the mother–infant relationship (the 'maternal brain'). However, which aspects of parenting are actually mother-specific and which rely on general cognitive abilities remains debated. For example, refuting earlier findings, a recent study demonstrated that fathers identify their own baby from their cries just as well as mothers. Here we show that this performance is independent not only of sex, but also of parenthood status. We found that mothers' ability to recognize their newborn from their cries increased rapidly within few days postpartum, with highly multiparous mothers performing better. However, both male and female non-parents could similarly recognize an assigned baby, even after a very short exposure. As in mothers, both the initial amount of experimental exposure to the baby's cries (learning opportunity) and prior experience of caring for infants (auditory expertise) affected participants' performance. We thus suggest that, rather than being female-specific or motherhood-dependent, the ability to recognize a baby from their cries derives from general auditory and learning skills. By being available to non-parents of both sexes, it may contribute to the caregiving flexibility required for efficient cooperative breeding in humans.